Síťový marketing: Nadějná pracovní příležitost pro ženy? - Irena Lištiaková; Lucie Jarkovská (Gender a Výzkum, 2014)
The authors analyse the discourse of Green Ways (GW), a company using multi-level marketing where women comprise the majority of distributors. The article shows that however multi-level marketing is advertised as a highly flexible form of employment suitable for those who want to combine family life with work, it is rather a way of marketing than an employment opportunity. A significant role in this business is played by women on parental leave who earn self-esteem based in the neoliberal values of self-reliance and entrepreneurial success, rather than financial income. The analysis links their ways of describing the character and benefits of selling GW products with the ideology presented in GW manuals for distributors. Using Bourdieu’s theory, the authors point out how GW constructs the symbolic oppositional binary in line with the neoliberal notion of an efficient individual.